Universiti Malaysia Pahang gets go-ahead for two new master’s programs - Irene, Wei Kiong Ting (2018)
Faculty of Chemical and Natural Resources Engineering, Universiti Malaysia Pahang (UMP) has become the first institution of higher learning in Malaysia to offer a new coursework program at Master level for mining and mineral technology. This curriculum structure is developed together with Minerals and Geoscience Department Malaysia and Malaysia Chamber of Mines, emphasizing on sustainable mining (up-stream) and mineral processing in the downstream. It is a program which provides learners with knowledge for the whole life cycle of the mine and on the related processes of it, from the start-up to closure of mine. Effectively, this broad range industry-oriented coverage is tailored to professionals irrespective of their academic background or work experience.